Sight correction : vision and blindness in eighteenth-century Britain - Mounsey, Chris, 1959- (Peculiar bodies : stories and histories, 2019)
"This book is both an empirical study of the mechanics, economics, and personal accounts of eye surgery and an exploration of the lives of historical people who were affected by vision and its failure, from eye-care specialists to blind writers who could not be cured"--